When dessert comes close: The effects of anticipating indulgent consumption and dietary restraint on healthy food preference at restaurants. (September 2020) - Oh, Ga-Eun (Grace)
Highlights: This study examines how anticipating indulgence affects healthy food preference. The effect of anticipating indulgence was moderated by consumers' dietary restraint. Anticipating indulgence reduced restrained eaters' healthy food preference. Anticipating indulgence tended to have an opposite effect among unrestrained eaters. Abstract: When dining in restaurants, diners often anticipate indulgent consumption, such as enjoying a dessert. This study examined the effects of anticipating such indulgence on preferences for healthy food among restrained and unrestrained eaters. Two experiments revealed that anticipating indulgent consumption reduced restrained eaters' preference for the immediate consumption of healthy food. Conversely, unrestrained eaters' expectation of indulgent consumption increased or did not change their preference for a healthy option. The interactive effect of indulgence anticipation and dietary restraint on healthy food preference held regardless of availability of nutrition information. The findings suggest that, despite increasing concern for healthy eating, restrained consumers ironically show a preference for unhealthy food options when anticipating a dessert consumption opportunity. The present study provides theoretical implications for consumption anticipation, sequential consumption, and dietary restraint, and practical implications for restaurateurs as well as for consumers, health professionals, and policymakers regarding healthy eating.